Correlation of the Automated Breast Volume Scanner (ABVS) and Hand-held Breast Ultrasound (HHUS) Findings - Bhothisuwan, Wilaiporn; Kimhamanon, Pramaporn (The Bangkok Medical Journal, 2012)
OBJECTIVES: To correlate the findings of Automated Breast Volume Scan (ABVS) and Hand-held Breast Ultrasound (HHUS), and to compare the benefits and drawbacks of each system as an adjunct to mammography. MATERIALS AND METHODS: A total of 212 adult female patients underwent mammography in the Breast Center of Wattanosoth Hospital in 2010 followed by ABVS and HHUS was interpreted and reported by radiologists immediately. ABVS was interpreted and recorded by one radiologist 3 months later. RESULTS: There were 504 lesions, interpreted as BIRADS 1 in 37 cases, BIRADS 2 (simple cyst) in 77 cases, BIRADS 3 in 63 cases, BIRADS 4 in 31 cases and BIRADS 5 in 4 cases. Both studies agreed in 306 lesions, there was agreement and ABVS showed additional lesions in 13 cases, the studies were not in agreement about 35 lesions. ABVS showed negative but HHUS showed positive in 24 lesions, HHUS showed negative but ABVS showed positive in 104 lesions although there were pitfalls in ABVS results in 24 lesions. CONCLUSION: In our study, despite having some drawbacks with nipple artifacts, ABVS showed significant improvement in detection of breast cancer in as compared to HHUS, uncovering 12 additional suspicious lesions, and excluding 3 suspicious lesions. Patients also benefit from a shorter, more comfortable examination without exposure to radiation agents or the need to hold their breath.